Penerapan Regresi Linier Sederhana dalam Peramalan Nilai Ekspor dan Impor di Provinsi Jawa Tengah - Muhammad Sulthan Madany,; Aini Mawar Mardiyah,; Lathifatul Aulia, (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
Central Java Province, one of the economic centers in Indonesia, has significant and diverse export and import activities. Understanding the patterns and factors that influence the value of exports and imports is expected to provide deeper insight into the economic condition of the region, as well as support more targeted policies. The simple linear regression method identifies the relationship between one independent variable and one dependent variable. The dependent variables used are the amount of goods produced (estimated exports) and local consumption (estimated imports). This study aims to estimate the value of exports and imports in Central Java Province using the simple linear regression method. The secondary data used in this study are from the Central Statistics Agency (BPS) and other related agencies during the 2019-2021 period. The resulting simple linear regression model shows a good level of accuracy with a high coefficient of determination (R²), indicating the model is able to explain variations in the value of exports and imports based on the specified dependent variable. Through regression analysis, this study established a significant relationship between time and changes in export and import values. The resulting model provides a strong basis for predicting future export and import values, so that it can be used as a reference for policy makers in formulating effective trade strategies at the regional level.